2019
DOI: 10.1037/com0000140
|View full text |Cite
|
Sign up to set email alerts
|

Deceased-infant carrying in nonhuman anthropoids: Insights from systematic analysis and case studies of bonnet macaques (Macaca radiata) and lion-tailed macaques (Macaca silenus).

Abstract: Existing models of attachment do not explain how death of offspring affects maternal behavior. Previous descriptions of maternal responsiveness to dead offspring in nonhuman anthropoids have not expounded the wide variation of deceased-infant carrying (DIC) behavior. Through the current study, we attempt to (a) identify determinants of DIC through a systematic survey across anthropoids, (b) quantitatively assess behavioral changes of mother during DIC, and (c) infer death perception of conspecifics. Firstly, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
73
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(78 citation statements)
references
References 86 publications
(154 reference statements)
4
73
1
Order By: Relevance
“…and S1.4 of Appendix S1), compared to two‐thirds that were not ( N = 39) (Appendix S3). This finding supports the results of Das et al () and suggests that contextual and sensory death cues aid the mother's understanding of the infant's condition, allowing her to terminate her parental investment. Surprisingly, in 14 cases, infants were abandoned alive after being injured by an infanticidal male.…”
Section: Primate Thanatology: Contemporary Reportssupporting
confidence: 89%
See 2 more Smart Citations
“…and S1.4 of Appendix S1), compared to two‐thirds that were not ( N = 39) (Appendix S3). This finding supports the results of Das et al () and suggests that contextual and sensory death cues aid the mother's understanding of the infant's condition, allowing her to terminate her parental investment. Surprisingly, in 14 cases, infants were abandoned alive after being injured by an infanticidal male.…”
Section: Primate Thanatology: Contemporary Reportssupporting
confidence: 89%
“…Das et al () found that carrying duration in cases of infanticide was significantly lower in comparison to other causes of death. They attribute three subcomponents typical of human death awareness to mothers carrying dead infants: repeated sensory investigation as a result of having ‘Causation’, handling of the inanimate infant and its defence as understanding ‘Cessation’, and progressive disinterest as possessing ‘Irreversibility’.…”
Section: Primate Thanatology: Contemporary Reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations of other behaviours by non-mothers lend further support to the social-bonds hypothesis. In three cases (7,10,11), an adult male-the friend of the mother and possible father of the dead infant in all cases-provided forms of post-mortem 'protection' involving 'guarding' behaviour by sitting near the corpse when the mother temporarily moved away, or by threatening perceived approaches to the corpse. Such guarding behaviour of an infant's corpse by an adult male has previously been reported in wild chacma baboons [27].…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis was not supported by a recent cross-species analysis of anthropoid primates (great apes, Old World and New World monkeys) that controlled for phylogenetic relatedness. The mother's age, the cause of the infant's death and the degree of the species' arboreality determined the length of time a corpse was carried [11].Intrinsic factors hypothesized to influence corpse carrying include cognitive, experiential and motivational/emotional processes. In the first case, the unawareness hypothesis suggests that the carrier is unaware or unsure that the infant is dead, and so they persist in performing infant-care behaviours, until awareness occurs.…”
mentioning
confidence: 99%